RESEÑA de : Temin, Peter. The Roman Market Economy. Princeton: Princeton University Press, 2012. - Alviz Fernández, Marco (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2015)
RESEÑA de : Temin, Peter. The Roman Market Economy. Princeton: Princeton University Press, 2012.